Penegakan Hukum Administrasi Terhadap Izin Usaha Industri Sebagai Instrumen YuridisPenaatan Lingkungan Hidup (Studi Tentang Pengawasan Dan Penerapan Sanksi Administrasidi Kota Semarang) - Moh. Hasyim (Fakultas Hukum Universitas Islam Indonesia, 2004)
Law enforcement in the form of control in the district Environmental Impact Assessment Agency which processes industrial permits in Semarang is still weak. This has occurred because the District Environmental Impact Assessment Agency'scontrolis not imple mented in an integrated or coordinated manner with other Associated Institutions. In terms of the object under control, basic issues like industrial permits and building permitshave not been made the objects of control.